HUBUNGAN ANTARA PENGETAHUAN DAN PENDIDIKAN IBU DALAM PEMBERIAN MAKANAN PENDAMPING ASI DI RUMAH BERSALIN CITRA PALEMBANG - Indah Rahmadaniah (Jurnal Kesehatan Abdurrahman, 2017)
A breastfeeding food companion is the giving of food supplements in addition to breast milk when the baby is 6 months of age. On 6-12 months of breast milk period, it only provides half or more nutrition to their children and on 12-14 months of breastfeeding period, it just provides their children with an extraordinary amount of nutrition to satisfy their bodily needs. That is why they need a breastfeeding food companion. The purpose of the study was to find out the correlation of mothers’ knowledge and education in the feeding of breastfeeding food companion at Childbirth Citra Palembang. The study was conducted in an analytic survey with a cross sectional approach. The population taken in this research was the mothers who had 6-8 months babies. The sampling technique was Accidental Sampling. The data were collected by simultaneous data using the questionnaire. The data analysis was calculated by the Chi-square statistic with the mean of α = 0.05. The results showed that there were 31 respondents (81.6%) given the breastfeeding food companion to their 6 months babies. There were 7 respondents (18.4%) given the breastfeeding food companion to their babies < 6 months. The conclusion there was a significant correlation between knowledge and the feeding of the breastfeeding food companion with value 0.006. There was also a significant correlation between education and feeding the breastfeeding food companion value 0.002. Makanan Pendamping ASI (MP-ASI) adalah pemberian makanan pendamping selain ASI saat bayi berusia 6 bulan. Pada usia 6-12 bulan ASI hanya menyediakan setengah atau lebih kebutuhan gizinya dan pada usia 12-14 bulan ASI hanya menyediakan sepertiga dari kebutuhan gizinya,untuk itu bayi perlu mendapatkan MP-ASI untuk mencukupi kebutuhan zat gizi tubuhnya . Tujuan penelitian adalah diketahuinya hubungan antara pengetahuan dan pendidikan ibu dalam pemberian MP-ASI di RB. Citra Palembang. Penelitian ini dilakukan secara survey analitik dengan pendekatan cross sectional. Populasi yang diambil pada penelitian ini yaitu ibu yang mempunyai bayi usia 6-8 bulan. Teknik pengambilan sampel yaitu secara Accidental Sampling. Data dikumpulkan secara observasi langsung dengan menggunakan kuesioner. Analisa data dilakukan dengan uji statistik Chi-Square dengan batas kemaknaan α = 0,05. Hasil penelitian menunjukkan terdapat 31 responden (81,6%) yang diberikan MP-ASI pada usia ≥ 6 bulan dan sebanyak 7 responden (18,4%) yang diberikan MP-ASI pada usia < 6 bulan. Kesimpulan ada hubungan yang signifikan antara pengetahuan dengan pemberian MP-ASI dengan nilai p value 0,006 dan ada hubungan yang signifikan antara pendidikan dengan pemberian MP-ASI dengan nilaip value 0,002.